A new hermit crab of the Paguristes tortugae complex (Crustacea: Anomura: Diogenidae), with a key to the western Atlantic species - Lima, Daniel José Marcondes [UNESP]; Santana, William [UNESP] (Taylor & Francis, 2017)
A new hermit crab species, Paguristes scarabinoi sp. nov. is described and illustrated based on specimens collected in Uruguay. The new species is assigned to the Paguristes tortugae species complex based on the characteristic dense fringe of long plumose setae present on ambulatory legs and dorsolateral margins of chelae. The new species can be differentiated from all other species currently placed in the P. tortugae complex by the combination of the following features: antennal flagellum with short and long setae on each article; antennular peduncles short to moderately long, not exceeding one-third of ocular peduncles including the corneas; dactyl of ambulatory legs long, slender, slightly convex and without a longitudinal sulcus flanked by corneous spines or spinules on the mesial face; and female brood pouch elongate, slender, blade-shaped. A key to the western Atlantic species of the P. tortugae complex is provided. http://zoobank.org/urn:lsid:zoobank.org:pub:4B3298F3-D5DF-40E5-A2AB-9B457AB8BE0E
Keywords: New species; Paguroidea; South America; south-western Atlantic; Uruguay